Kemampuan Pemecahan Masalah Siswa Kelas VIII SMP Negeri 17 Mataram Pada Materi Pola Bilangan Yang Menggunakan Pembelajaran Melalui WhatsApp Tahun Pelajaran 2021/2022: Kemampuan Pemecahan Masalah Siswa Kelas VIII SMP Negeri 17 Mataram Pada Materi Pola Bilangan Yang Menggunakan Pembelajaran Melalui WhatsApp - Septiarini, Eka Safitri (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2025)
This study aims to describe the problem-solving abilities of class VIII students of SMP Negeri 17 Mataram in the matter of number patterns using learning via WhatsApp for the 2021/2022 academic year and identify problems encountered by teachers and students in the learning process via WhatsApp. This research is a qualitative descriptive study. The research sample was selected using a purposive sampling technique, namely class VIII A as many as 26 students. The data collection technique used was giving tests, distributing questionnaires and student responses, as well as interviews. Based on the results of the descriptive analysis, it shows that the average problem solving ability of student is 62.10 which is included in the less detailed category, 15 students or 57.70% of students with poor problem-solving abilities (not yet able to complete all stages), 3 students or 11.54% of students with sufficient problem-solving abilities (not yet able to perform the stages of finding strategies, using strategies, and looking back completely), 2 students or 7.69% with good problem-solving abilities (not yet able to carry out stages of understand the problem and looking back completely), 6 students or 23.07% of students with very good problem solving skills (not yet able to do the stages of looking back completely). There are obstacles encountered by teachers in the learning process via WhatsApp, namely studens’ internet connection, some students do not know how to reply answer correctly, difficulties in explaining the stage of problem solving properly. While the obstacles encountered by students namely, internet network, motivation, giving assignments, and understanding of the stages of problem solving, as well subject matter.